(3GdbGfhf aj GdWHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hGdSdGe Ydi YHGOg GdeDefjf hEP bO hajfG hYOfG ef JUfja cJHfG ai GdWH GdJi GdChd efgG GdCUhd GdcdjI hGdKGfi efgG GdeLehY ai GdCOhjI GdeaQOI Gdaf GdChd ef Gdafhf GdSHYI cdGe cdj ai GdMejGJ s
(3BNQgG (B:s
(3CUGHY GdQLd YdGLgG ai GdcSQ hGdNdY YdGLg CUGHY GdjOhQ HeG ShGgG GdeLHQ Je s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1311s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs